Methodology and algorithm for assessing the impact of economic factors on the real estate market of Ukraine (Economics and region, 2023)
The article is devoted to the analysis of methodology and the development of an algorithm for assessing the impact of economic factors on the real estate market of Ukraine. An analysis of economic factors affecting the real estate market of Ukraine is carried out, as a result of which a number of indicators that have a direct influence and shape the trends of the real estate market of Ukraine are singled out, namely: the index of rates for deposits of natural persons, the index of price changes in construction, the discount rate of the National Bank of Ukraine, average prices on the primary real estate market. Modern methods of forecasting the real estate market are summarized and characterized, including the following: methods using average characteristics (extrapolation based on the average level of the series, extrapolation on the average absolute growth, extrapolation on the average growth rate), mechanical methods (moving average method, weighted moving average method, exponential smoothing method, median smoothing), analytical methods (methods regression analysis – the method of sequential differences (Tintner), method of growth characteristics; adaptive methods – Brown, Brown-Mayer Holt, Holt-Winters model), software methods (within the Statgrafics, phyton, streamline, etc. software packages). It is argued that the key to successful forecasting is the development of an algorithm that systematizes approaches and forms a clear vision of the sequence of necessary stages and directly applied methods at each of them. Therefore, the algorithm for assessing the impact of economic factors on the real estate market of Ukraine has been developed, within which it is proposed to use a set of methods, including checking for abnormal values (Irvin’s method), checking time series for stationarity (Forster-Stewart method), identifying trends, and carrying out their correction, forecasting (Brown-Meier method) using Excel and Statgraphics software packages, checking the used methods for the relevance of the forecast in relation to already available data, assessing its realism and the possibility of using these forecasts in future transactions on the real estate market of Ukraine.
Keywords: construction; factor analysis; forecasting; housing; modelling; real estate market